Emodin modulates epigenetic modifications and suppresses bladder carcinoma cell growth. Issue 3 (20th September 2013) - Cha, Tai‐Lung; Chuang, Mei‐Jen; Tang, Shou‐Hung; Wu, Sheng‐Tang; Sun, Kuang‐Hui; Chen, Tzu‐Ting; Sun, Guang‐Huan; Chang, Sun‐Yran; Yu, Cheng‐Ping; Ho, Jar‐Yi; Liu, Shu‐Yu; Huang, Shih‐Ming; et al.
Abstract The deregulation of epigenetics was involved in early and subsequent carcinogenic events. Reversing cancer epigenetics to restore a normal epigenetic condition could be a rational approach for cancer treatment and specialized prevention. In the present study, we found that the expression levels of two epigenetic markers, histone H3K27 trimethylation (H3K27me3), was low but histone H3S10 phosphorylation (pH3Ser10) was high in human bladder cancer tissues, which showed opposite expression patterns in their normal counterparts. Thus, we investigated whether a natural product, emodin, has the ability to reverse these two epigenetic modifications and inhibit bladder cancer cell growth. Emodin significantly inhibited the cell growth of four bladder cancer cell lines in a dose‐ and time‐dependent manner. Emodin treatment did not induce specific cell cycle arrest, but it altered epigenetic modifications. Emodin treatment resulted in the suppression of pH3Ser10 and increased H3K27me3, contributing to gene silencing in bladder cancer cells. Microarray analysis demonstrated that oncogenic genes including fatty acid binding protein 4 (FABP4) and fibroblast growth factor binding protein 1 (HBP17), RGS4, tissue inhibitor of metalloproteinase 3 (TIMP3), WNT5b, URB, and collagen, type VIII, alpha 1 (COL8A1) responsible for proliferation, survival, inflammation, and carcinogenesis were significantly repressed by emodin. The ChIP assays also showed that emodin increased H3K27me3 but decreased pH3Ser10 modifications on the promoters of repressed genes, which indicate that emodin reverses the cancer epigenetics towards normal epigenetic situations. In conclusion, our work demonstrates the significant anti‐neoplastic activity of emodin on bladder cancer cells and elucidates the novel mechanisms of emodin‐mediated epigenetic modulation of target genes. Our study warrants further investigation of emodin as an effective therapeutic or preventive agent for bladder cancer. © 2013 Wiley Periodicals, Inc.